5 steps on recognizing alcoholic cans / Mohd Nasiruddin Abdul Aziz ... [et al.] - Abdul Aziz, Mohd Nasiruddin; Ahmad, Ahmad Khairul Azizi; Abdullah, Muhammad; Ramlie, Mohd Khairulnizam; Rahaman, Ashraf Abdul (2024)
This research investigates the confusion faced by Muslim consumers in Malaysia when differentiating between alcoholic and non-alcoholic canned beverages due to similar design elements, despite alcohol being illegal for Muslims. Instances of mixed placement of these beverages on store shelves have been reported, leading to consumer confusion. The study aims to identify the confusing design elements and develop a new visual sign to help consumers accurately identify alcoholic beverages. Utilizing a mixed-method approach, qualitative data were gathered through questionnaire surveys conducted during the pilot-test, pre-test, and post-test stages, while quantitative data were obtained from literature review, in-depth interviews, direct observation, and visual analysis. Data were analyzed and integrated using triangulation. The findings revealed five key design elements contributing to the confusion: pattern, color, brand, images, and typography. This research proposes a new visual indicator to improve recognition and prevent accidental consumption of alcoholic beverages by Muslim consumers.